Wimax Performance Impacts in Multi-Cell Deployments - Chen, Yejian; Halbauer, Hardy; Schaich, Frank (Communications - Scientific letters of the University of Zilina, 2019)
This paper presents the application of the multiple antenna schemes beamforming (BF) and Multiple Input Multiple Output (MIMO) in the broadband wireless access system WiMAX. The evaluation considers the competing performance demands on link robustness and peak data rate. Configurations for both uplink and downlink are discussed. We conclude that future wireless communications will rely on diverse and adaptive multiple antenna schemes to meet their requirements, in particular in the presence of strong co-channel interference.